PERAN TEKNOLOGI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN BAHASA INGGRIS DI JENJANG SEKOLAH DASAR - Siti Yuni Khairum; Adrias, Adrias; Zulkarnaini, Aissy Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
English language learning in Indonesian primary schools still faces challenges, particularly in reading, writing, pronunciation, and spelling skills. The lack of interactive media and low student motivation are also major obstacles. This study aims to analyze the role of technology in improving the quality of English language learning in primary schools. The research uses a descriptive-qualitative method with a literature review approach, gathering data from relevant journals and academic articles. The findings show that technology, such as educational apps, learning videos, and interactive games, can make learning more engaging and effective, while also allowing students to learn independently. Technology also helps teachers in organizing materials and managing classrooms more efficiently. This study concludes that integrating technology has great potential to improve student learning outcomes and the relevance of English language learning in primary schools.